Stock Transaction Manipulation - Rahima Br Purba; Junawan (International Journal of Management, Economic and Accounting, 2025)
The Indonesian capital market continues to grow rapidly with the increasing number of retail investors in recent years. However, this growth is also accompanied by the phenomenon of stock transaction manipulation, especially in small-cap stocks or known as "gorengan" stocks. This manipulation practice creates price distortions that do not reflect the company's fundamentals, thereby harming investors and diminishing trust in the integrity of the capital market. This research aims to identify transaction patterns of risky stocks and penny stocks, analyze the factors causing stock transaction manipulation, and evaluate its impact on the stability of the capital market in Indonesia. The research method used is qualitative descriptive with a literature review approach. Data were obtained from reports by the Indonesia Stock Exchange (IDX), the Financial Services Authority (OJK), academic journals, and trusted economic news sources. The analysis techniques used include descriptive analysis and content analysis with data source triangulation to enhance the validity of the findings. The research results indicate that the lack of transparency from issuers, suboptimal regulations, and low financial literacy among retail investors are the main factors that enable stock manipulation. The impacts include high price volatility, potential significant losses for investors, and a decline in trust in the capital market. To address this issue, strengthening regulations, utilizing early detection systems based on data analytics technology and artificial intelligence (AI), as well as providing financial education for retail investors to enhance their understanding of investment risks, are necessary. With these measures, it is hoped that the stability and integrity of the Indonesian capital market can be better maintained.